2009
DOI: 10.1007/s10552-009-9303-5
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle, dietary, and medical history factors associated with pancreatic cancer risk in Ontario, Canada

Abstract: Objectives Pancreatic adenocarcinoma has one of the worst survival rates of all the cancers. Established risk factors for this malignancy are smoking, body mass index (BMI) and family history of pancreatic cancer. Findings are inconsistent regarding pancreatitis, diabetes, allergies, intake of fruit, vegetables, red meat, alcohol, caffeine, vitamin C, calcium, and folate supplements. Possible pancreatic cancer risk factors were evaluated within the population-based Ontario Pancreas Cancer Study. Methods Path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
86
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 40 publications
(63 reference statements)
3
86
0
Order By: Relevance
“…Inverse associations have been reported between allergies and pancreatic cancer in a number of studies [12,[39][40][41], with a pooled OR of 0.82 (95% CI = 0.68-0.99) in a recent meta-analysis [39]. A protective effect of allergy on pancreatic cancer risk is speculated to be due to the hyperactivity of the immune system of allergic individuals [39,40].…”
Section: Discussionmentioning
confidence: 96%
“…Inverse associations have been reported between allergies and pancreatic cancer in a number of studies [12,[39][40][41], with a pooled OR of 0.82 (95% CI = 0.68-0.99) in a recent meta-analysis [39]. A protective effect of allergy on pancreatic cancer risk is speculated to be due to the hyperactivity of the immune system of allergic individuals [39,40].…”
Section: Discussionmentioning
confidence: 96%
“…However, many of these studies included proxy respondents, thus increasing the likelihood that information bias may have affected results. Of the case-control studies that did not include proxies (10,12,53,(56)(57)(58)(59)61), inverse associations with fruit and/or vegetable intake were reported by most, but not all (10,57,59), with risk reductions ranging from 40% to 46% (10,12,53,56,58) for the highest fruit intakes versus the lowest and from 33% to 53% for the highest vegetable intakes versus the lowest (12,53,56,59,61). However, bias due to differential diet recall or differential participation rates related to fruit and vegetable consumption between cases and controls is possible in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of pancreatic cancer in relation to fruit and vegetable consumption has been examined in over 35 epidemiologic studies (4,(7)(8)(9)(10)(11)(12)(13), and most have found inverse associations with fruit and/or vegetable intake. However, associations have been stronger in case-control studies than in cohort studies, and most case-control studies have relied on proxy respondents for exposure information, with proportions of proxies exceeding 50% of the case series in many studies (14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…A family history of PC is another risk factor [7][8][9][10][11][12][13][14][15][16]. Familial PC (FPC), which is defined as the presence of two first-degree relatives (FDRs) with PC and is not associated with known hereditary syndromes, accounts for 4-10% of all PC cases [7] (similar incidences in western countries and Japan [17]) ( Table 1) [17][18][19][20][21][22][23][24][25][26][27][28]. Some inherited syndromes also show higher risks, such as Peutz-Jeghers syndrome (PJS) [29], hereditary pancreatitis [30], familial atypical multiple mole melanoma (FAMMM), and hereditary breast-ovarian cancer (HBOC) [11] (Table 2).…”
Section: Abbreviationsmentioning
confidence: 99%
“…Since the 1990s, the risk of a family history of PC has been assessed by case-control and cohort studies in many countries (Table 1) [17][18][19][20][21][22][23][24][25][26][27][28]. In case-control studies, the incidence of FPC among all cases of PC was 4-10% (5 [23]-7% [17] in Japan), and the odds ratio (OR) or relative risk (RR) for PC incurred by having a firstdegree relative (FDR) with PC was 2.09 [23]-5.25 [18].…”
Section: Abbreviationsmentioning
confidence: 99%